(untitled) (Journal of Forest and Livelihood, 2005)
The authors situate Nepal’s forestry policy changes in the wider socio-political context of the country in different political regimes in the history, from pre-unification period to the present. The paper provides a rich and insightful account of specific policy practices and institutions – ranging from indigenous forest management, involvement of state-owned timber company The Timber Corporation of Nepal (TCN), governmental attempts at addressing landlessness (sukumbasi) and forest encroachment, and community forestry. It reveals how political and bureaucratic elites have manipulated the forest policies and practices for their benefits despite the rhetoric of periodic change/improvement. The authors however seem to be less clear in their main argument on the possible institutional modality of forest management, and are often inconsistent about their political and moral viewpoints on the issue. In this note, we seek to highlight some of the important gaps and the emergent themes that deserve further analysis and reflections.